„Zaszczytnie odznaczeni na polu naukowem”. Obraz polskich uczonych i badaczy w „Wędrowcu” (1863–1906) - Pietrzak , Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
The aim of the article is to present the linguistic image of Polish scholars and research- ers whose profiles, biographies and obituaries were published in the Warsaw weekly newspaper Wędrowiec (Traveller) in the second half of the nineteenth century. Ana- lysing the collected texts, the author distinguished a set of seven aspects which were taken into account by the journalists of Wędrowiec to present the profiles of the schol- ars. Those aspects are the following: the subject of research, scientific achievements, journalistic and publishing activities, didactic and educational activities, science-pro- moting activities, organisational activities, awards and distinctions. They were deter- mined by the points of view adopted by the authors of the texts. There are three domi- nant points of view: the one of an expert, a Pole and a positivist. These points of view coexist and complement each other. The expert and specialist informed the reader in detail about the scientific career and achievements of the scholars. The Polish publi- cist expressed his joy at the international success of his countrymen. He observed their research and scientific achievements with attention; especially those that influenced the development of fields important for the country. The positivist and journalist noticed and emphasised the utilitarian dimension of the scientific and research activities of the scholars.